Pendampingan Manajemen Bisnis untuk Usaha Mikro Kecil dan Menengah Keripik Pisang Banana Bobs - Aldo Koesurya; Ardyanto Kang; Bill Angelo; Clara Monica Rahardja; Felicia; Lisa Carissa; Octavius William; Titin Pranoto (Rahmatan Lil 'Alamin Journal of Community Services, 2023)
This community service activity (PKM) is a business management mentorship that aims to increase efficiency and effectiveness in the productivity of the selected partner business, namely Banana Bobs. Banana Bobs' product is banana chips, and has great potential because it is in the tourist area. Business management mentoring consists of identifying problems and offering solutions to Banana Bobs in terms of operations, marketing, human resources and finance. The methods used in this activity include field observations, interviews, training, and practicing directly with Banana Bobs' partners. This PKM activity contributes to Banana Bobs to increase competitiveness in competition with other micro, small, and medium enterprises (MSMEs) so that it can grow rapidly and become a product that is well recognized by the public in Indonesia.